Capital Structure Mediates the Effect of Profitability and Company Size on Company Value in Hospitality Companies Listed on the IDX for the 2019-2022 Period - Nurbaeti, Nurbaeti; Ratnaningtyas, Heny; Swantari, Anita (At-Tadbir : jurnal ilmiah manajemen, 2025)
This research aims to determine and analyze the influence of profitability and company size on company value through company value for 2019-2022. This type of research is descriptive quantitative, which was processed with Eviews using the path analysis method, namely direct and indirect influence. The population in this research is all hotel companies in Indonesia. The sample consisted of 10 hotel companies listed on the Indonesian Stock Exchange. The sampling technique uses purposive sampling. The partial research results show that profitability significantly affects capital structure and company value. A high ROE in hotel companies significantly affects capital structure because they can obtain loans at lower interest rates, show permits, and have the option to use less debt. A high ROE reflects management's efficiency in using capital and is attractive to investors looking for a high rate of return.